New organosoluble aromatic poly(esterimide)s containing pendent pentadecyl chains: synthesis and characterization - Sadavarte, Nilakshi V.; Patil, Sachin S.; Avadhani, C. V.; Wadgaonkar, Prakash P. (High Performance Polymers, 2013)
A new diimide dicarboxylic acid, namely 2,2-(4-pentadecyl-1,3-phenylene)bis(1,3-dioxoisoindoline-5-carboxylic acid), containing preformed imide rings and pentadecyl chain, was synthesized by the reaction of 4-pentadecylbenzene-1,3-diamine with trimellitic anhydride. A series of new aromatic poly(esterimide)s (PEIs) was synthesized using diphenylchlorophosphate-activated direct polycondensation of 2,2-(4-pentadecyl-1,3-phenylene)bis(1,3-dioxoisoindoline-5-carboxylic acid), with five commercially available bisphenols, namely 4,4-isopropylidenediphenol (I), 4,4-(hexafluoroisopropylidene)diphenol (II), 4,4-oxydiphenol (III), 4,4-biphenol (IV), and 4,4-(9-fluorenylidene)diphenol (V) in the presence of pyridine and lithium chloride. Inherent viscosities of PEIs were in the range 0.54-0.83dLg(-1) in chloroform (CHCl3) at 30 +/- 0.1 degrees C. PEIs containing pendent pentadecyl chains were soluble in organic solvents such as CHCl3, m-cresol, N, N-dimethylacetamide, 1-methyl-2-pyrrolidinone, pyridine, and nitrobenzene. Tough, transparent, and flexible films of PEIs could be cast from their CHCl3 solutions. PEIs exhibited glass transition temperature in the range 145-198 degrees C. The temperature at 10% weight loss of PEIs, determined by thermogravimetric analysis under the nitrogen atmosphere, was in the range of 450-470 degrees C indicating good thermal stability.
Keywords: pendent pentadecyl chains; Polycondensation; Polyimide; Preformed imide rings; Thermogravimetric analysis

New atom transfer radical polymerization initiator based on phenolphthalein for the synthesis of bis-allyloxy functionalized polystyrene macromonomers - Patil, Sachin S.; Menon, Shamal K.; Wadgaonkar, Prakash P. (Polymer International, 2015)
A new atom transfer radical polymerization (ATRP) initiator, namely 2-(1,1-bis(4-(allyloxy)phenyl)-3-oxoisoindolin-2-yl)ethyl 2-bromo-2-methylpropanoate, was synthesized starting from phenolphthalein, a commercially available and an inexpensive chemical. Well- defined bis-allyloxy functionalized polystyrene macromonomers (M-n,M-GPC 4800-11 700gmol(-1)) with controlled molecular weight and narrow molecular weight distribution (1.05-1.09) were synthesized using ATRP by varying the monomer to initiator feed ratio. The presence of allyloxy functionality on polystyrene was confirmed by Fourier transform infrared and H-1 NMR spectroscopy. A kinetic study of polymerization revealed pseudo-first-order kinetics with respect to monomer consumption. Initiator efficiency was found to be in the range 0.80-0.95. Matrix-assisted laser desorption ionization time of flight spectra showed a narrow molecular weight distribution with control over the molecular weight. The reactivity of the allyloxy groups on polystyrene was successfully demonstrated by quantitative photochemical thiol-ene click reaction with benzyl mercaptan as the model thiol reagent. Furthermore, the thiol-ene click reaction was exploited to introduce other reactive functional groups such as hydroxyl and carboxyl by reaction of ,-bis-allyloxy functionalized polystyrene with 2-mercaptoethanol and 3-mercaptopropionic acid, respectively. (c) 2014 Society of Chemical Industry
Keywords: atom transfer radical polymerization; bis-allyloxy functionalized polystyrene; functional initiator; phenolphthalein; thiol-ene click reaction